Potential Market Willingness to Pay Through Edutourism Plan at CV. Damarayu Malang District - Mutiaristi, Like; Anindita, Ratya; Nugroho, Condro Puspo (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2017)
Edutourism is a necessity for kindergarten school, and enteprise can develop edutourism for kindergarten school as their potential market. This fact is crucial to observe to encounter potential market with enteprise that can supply their needs and both can get profit from the edutourism. By that background, this research are going to find valuation of the edutourism plan by potential market willingness to pay (WTP), to know factors that influence potential market WTP and to know potential market segmentation that declare willing to pay the edutourism. This research uses quantitative approach, analyzed by contingent valuation method and logistic regression analysis. The potential market in this research are kindergarten school in Pakisaji sub-district that have outingclass program. The finding revealed that economic value of the edutourism is more than the price target. Factors that influence potential market WTP are teachers education background, school fee per month, and ability to pay. Segmentation of the edutourism plan are kindergarten school with standard teacherâs education background in bachelor degree, categorized in low price school fee and already have ability to pay the edutourism.